The bioarchaeology of individuals - Stodder, Ann Lucy Wiener; Palkovich, Ann M.; Larsen, Clark Spencer (Bioarchaeological interpretations of the human past., 2012)
Spanning more than 4000 years of human history and focusing on individuals who lived between 3200 BC and the 19th century, the essays in this book examine the daily lives of nomads, warriors, artisans, farmers, and healers by constructing profiles of the lives of specific individuals whose remains were excavated from archaeological sites.